2006
DOI: 10.1262/jrd.17047
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Calcium/Calmodulin-dependent Protein Kinase II during Oocyte Activation in the Rat

Abstract: Abstract. Increases in intracellular Ca2+ are required for oocyte activation and subsequent development. Calmodulin-dependent protein kinase II (CaMKII) plays a crucial role in oocyte activation. However, how CaMKII is regulated during this process is not well characterized. We show here for the first time in rat oocytes that CaMKII is phosphorylated during oocyte activation. CaMKII phosphorylation was suppressed by KN93, a CaMKII inhibitor, but not KN92, which is the inactive analogue of KN93. Electrical stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
(55 reference statements)
1
18
0
Order By: Relevance
“…Two articles supporting our findings have been published lately; Ito et al (2006) have shown that the CaMKII phosphorylation occurring during egg activation can be suppressed by KN93, a CaMKII inhibitor. They claimed that this phosphorylation is involved in inactivation of p34 cdc2 kinase and degradation of Mos.…”
Section: Marcks Mediates Cortical Granules Exocytosissupporting
confidence: 82%
See 1 more Smart Citation
“…Two articles supporting our findings have been published lately; Ito et al (2006) have shown that the CaMKII phosphorylation occurring during egg activation can be suppressed by KN93, a CaMKII inhibitor. They claimed that this phosphorylation is involved in inactivation of p34 cdc2 kinase and degradation of Mos.…”
Section: Marcks Mediates Cortical Granules Exocytosissupporting
confidence: 82%
“…The involvement of CaMKII in egg activation events has been the topic of many studies conducted lately. While CaMKII involvement in promoting RMII is well established (Markoulaki et al 2003, Sun 2003, Madgwich et al 2005, Ito et al 2006, Knott et al 2006, its involvement in CGE is still controversial.…”
Section: Marcks Mediates Cortical Granules Exocytosismentioning
confidence: 99%
“…Ito et al [13,14] showed that ovulated rat oocytes, especially those from the Wistar strain, cannot be arrested at metaphase II due to the loss of activity of p34 cdc2 kinase maintained by high activity of Mos/MeK/MAPK pathways which in turn are negatively regulated by Ca 2+ -dependent proteasome. Therefore, incubation of rat oocytes in Ca 2+ -free conditions or addition of BAPTA-AM, a Ca 2+ chelator, to the incubation medium effectively inhibited OSA [10,11,14].…”
Section: Discussionmentioning
confidence: 99%
“…Under the conditions employed in this study, most mature WMN/Nrs females showed 4-day estrous cycles. An average of 12.2 embryos (range 6-17 embryos) and an average litter size of 10.2 (n=31, range [5][6][7][8][9][10][11][12][13][14] were observed during natural ovulation and mating (Ueno M., personal communication). Body weights of WMN/Nrs females were 30.2 ± 0.5 g at 3 weeks of age, 50.7 ± 0.8 g at 4 weeks, 76.2 ± 1.2 g at 5 weeks, 97.9 ± 1.1 g at 6 weeks, 117.0 ± 1.4 g at 7 weeks, 134.5 ± 1.6 g at 8 weeks and 147.0 ± 2.0 g at 9 weeks of age (n=15) (Yamada Y., personal communication).…”
Section: Animalsmentioning
confidence: 99%
“…In general, the nuclear status of in vitro matured canine oocytes is evaluated using [27][28][29][30]. It has also been demonstrated that p34 cdc2 kinase activity decreases depending on the length of the culture period, a process designated 'aging' after the progression to MII [31][32][33][34]. This aging is involved in abnormal formation of pronuclei after in vitro fertilization or artificial activation in pigs [35,36].…”
mentioning
confidence: 99%